China’s Perceptions of Russia during the Ukraine Conflict - Srikanth Kondapalli (Vestnik MGIMO-Universiteta)
The ongoing Russian military operation in Ukraine since February 2022 has presented significant challenges to China's foreign and security policies, as well as its economic and technological ties with the West. Initially, China refrained from criticizing Russia's military actions and adopted a "neutral" or "independent" stance in response to Western criticism. However, China was taken aback by the protracted nature of the conflict and Russia's inability to successfully conclude its military operation. This raised concerns within China, considering its own situation of potentially reunifying with Taiwan through military means if necessary. While there are distinctions between the situations in Ukraine and Taiwan, the initial speculation of China conducting military operations against Taiwan has gradually diminished, although military pressure on Taiwan remains. The conflict in Ukraine has also caused internal divisions within China and has had an impact on its relations with the West, which are crucial for China's rise on the global stage. This article aims to examine China's interests and positions regarding the ongoing Ukrainian conflict, the implications for its relations with Russia, and the opportunities and challenges that China faces in the current situation. The article employs an inductive approach, analyzing China's predicaments at four levels: perceptions within the decision-making bodies of the Communist Party, the foreign ministry, think-tanks, and the media community. It argues that in conjunction with China's economic contraction resulting from the COVID-19 pandemic, the Russian military operation has prompted China to seriously contemplate how to safeguard its national interests, particularly with regard to Taiwan and its strategic objectives of attaining a prominent global position. These considerations carry medium to long-term implications for the evolving regional and global orders. In conclusion, the article briefly discusses the implications of these developments on India, shedding light on the broader regional dynamics influenced by China's response to the Ukrainian conflict.